Canadians' experiences of alternative protein foods and their intentions to alter current dietary patterns - Gumataw Kifle Abebe; Mariam R. Ismail; Kathleen Kevany; Hiwot Abebe Haileslassie; Treasa Pauley (Journal of Agriculture and Food Research)
Despite established evidence about the environmental and health benefits of alternative protein foods (APF), considerable knowledge gaps and misconceptions remain toward APF. Drawing on a national survey (1800+ responses), the study explores Canadians' experiences of APF and intentions to alter current dietary patterns focusing on four APF – plant-based alternative proteins (PBAP) – plant-based (PB) milk, PB meat, lab-grown (LG) meat, and other alternative proteins (OAP) – and two animal-based foods (ANBF)– milk and meat. Data were collected based on a proportional stratified sampling method from all regions of Canada and analyzed using econometric models. While PB milk was the most consumed APF, followed by PB meat, LG meat was the least tried among participants. Perceived complexity of APF discouraged individuals from cutting back on ANBF, while increasing the consumption of APF. Perceived relative advantage was positively related to the adoption of APF. Perceived compatibility strongly influenced individuals’ adoption of PB meat and OAP. Likewise, perceived trialability significantly influenced the adoption of PB milk and PB meat. Despite the perception that APF may have high health related risks associated with processing, additives, calorie and sugar content, this did not prevent individuals from consuming PB milk and OAP. However, perceived risks did affect intentions to alter dietary patterns in the next 12 months. Additionally, meat attachment and sustainability orientation significantly predicted current consumption decisions of APF and intentions to alter dietary patterns. Although sustainability orientation motivates dietary changes, it did not always lead to extreme shifts. Finally, several demographic variables (age, gender, and education), dietary preferences (being omnivore), and residential area and region had influence on current consumption decisions and future intentions. In conclusion, by controlling several factors and through a comparative analysis of various protein sources, the study offers insights into the interplay of innovation-adoption characteristics, perceived risks, meat attachment and sustainability orientation in understanding dietary choices and provides some implications for industry stakeholders and policies promoting APF.